2001
DOI: 10.1021/ef000205t
|View full text |Cite
|
Sign up to set email alerts
|

Si-MCM41 Supported Sulfated Zirconia and Nafion for Ether Production

Abstract: Various unsupported and supported sulfated zirconia and Nafion catalysts were prepared and investigated for etherification of C6 olefins with methanol. Supported sulfated zirconia and Nafion generally show higher activity than unsupported sulfated zirconia and Nafion. The nature of the support and catalyst preparation techniques were found to affect the catalytic activity. Mesoporous Si-MCM41 with high surface area was the best support for the acid catalysts. Si-MCM41 supported sulfated zirconia and Nafion cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…pentene (2,4,4TM1P), and 2,4,4-trimethyl-2-pentene (2,4,4TM2P), with methanol using 10 weight percent dry Amberlyst produced a significant amount of higher ethers, such as 2 -methoxy-2,3-dimethylbutane (2MO2,3DMB) and 2 -methoxy-2,4,4-trimethylpentane (2MO2,4,4TMP) along with 2 -hydroxy-2,3-dimethylbutane. The detectable amount of alcohol product produced in the course of etherification indicates that a small amount of water was present in the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pentene (2,4,4TM1P), and 2,4,4-trimethyl-2-pentene (2,4,4TM2P), with methanol using 10 weight percent dry Amberlyst produced a significant amount of higher ethers, such as 2 -methoxy-2,3-dimethylbutane (2MO2,3DMB) and 2 -methoxy-2,4,4-trimethylpentane (2MO2,4,4TMP) along with 2 -hydroxy-2,3-dimethylbutane. The detectable amount of alcohol product produced in the course of etherification indicates that a small amount of water was present in the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this progress report will consist of a summary of these final activities on our etherification project, prior to redirection. Detailed results are available in a series of papers that have been submitted for publication (1)(2)(3)(4)(5) .…”
Section: University Of Utahmentioning
confidence: 99%
“…Because of the potential importance of higher ethers as high production volume (HPV) fuel blend components, a number of studies of the preparation of MtHxE and MtOcE have appeared recently in the literature. 8,10,11,[13][14][15] As was the case with MtBE, the introduction of these ethers into fuel supplies also guarantees their introduction into the environment. It is, therefore, of interest to assess the potential risk that these higher ethers may pose to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, they generally have low BET surface areas (\50 m 2 /g) [2], and preparation of resin-silica nanocomposite is good way to increase BET surface area and accessibility for acidic sites of resins [163][164][165][166][167][168][169][170]. For examples, Wang et al reported the incorporation of Nafion to ordered mesoporous silica of MCM-41 by sol-gel technique [165]; Corma and coworkers reported the synthesis of hybrid organic-inorganic mesoporous materials with terminal perfluorinated sulfonic groups [167,168]. These resin modified mesoporous solid acids showed remarkable catalytic activities in a series of esterification [163][164][165][166][167][168][169].…”
Section: Resins Modified Mesoporous Silicasmentioning
confidence: 99%
“…For examples, Wang et al reported the incorporation of Nafion to ordered mesoporous silica of MCM-41 by sol-gel technique [165]; Corma and coworkers reported the synthesis of hybrid organic-inorganic mesoporous materials with terminal perfluorinated sulfonic groups [167,168]. These resin modified mesoporous solid acids showed remarkable catalytic activities in a series of esterification [163][164][165][166][167][168][169].…”
Section: Resins Modified Mesoporous Silicasmentioning
confidence: 99%